Nanoarchitectonics Design Strategy of Metal–Organic Framework and Bio-Metal–Organic Framework Composites for Advanced Wastewater Treatment through Adsorption - Agamendran, Nithish; Uddin, Maseed; Yesupatham, Manova Santhosh; Shanmugam, Mariyappan; Augustin, Ashil; Kundu, Tanay; Kandasamy, Ramani; Sasaki, Keiko; Sekar, Karthikeyan (Langmuir, 2024)
Freshwater depletion is an alarm for finding an eco-friendly solution to treat wastewater for drinking and domestic applications. Though several methods like chlorination, filtration, and coagulation-sedimentation are conventionally employed for water treatment, these methods need to be improved as they are not environmentally friendly, rely on chemicals, and are ineffective for all kinds of pollutants. These problems can be addressed by employing an alternative solution that is effective for efficient water treatment and favors commercial aspects. Metal organic frameworks (MOFs), an emerging porous material, possess high stability, pore size tunability, greater surface area, and active sites. These MOFs can be tailored; thus, they can be customized according to the target pollutant. Hence, MOFs can be employed as adsorbents that effectively target different pollutants. Bio-MOFs are a kind of MOFs that are incorporated with biomolecules, which also possess properties of MOFs and are used as a nontoxic adsorbent. In this review, we elaborate on the interaction between MOFs and target pollutants, the role of linkers in the adsorption of contaminants, tailoring strategy that can be employed on MOFs and Bio-MOFs to target specific pollutants, and we also highlight the effect of environmental matrices on adsorption of pollutants by MOFs.